1944
DOI: 10.1002/hlca.194402701157
|View full text |Cite
|
Sign up to set email alerts
|

Über Alkyl‐(β‐oxy‐β‐aryl‐äthyl)‐sulfide und Dialkyl‐(β‐oxy‐β‐aryl‐äthyl)‐sulfonium‐salze

Abstract: Zur Analyse wurde zunachst im Hochvakuum bei 50° getrocknet, unmittelbar vor der Verbrennung noch 10 Stunden bei 200 uber P,O, nachgetrocknet und im Schweinchen eingewogen.3,656 mg Subst. gaben 6,510 mg CO, und 2,676 mg H1O

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…The correct connectivity was established by Spielman (1935). This amine is chiral, and the resolution of the base into its enantiomeric forms was first accomplished by Prelog & Wieland (1944). It is interesting to note that this was the first amine, chiral solely due to the difficulty of inversion at N, to be resolved.…”
Section: Introduction the Title Compound First Prepared Bymentioning
confidence: 97%
“…The correct connectivity was established by Spielman (1935). This amine is chiral, and the resolution of the base into its enantiomeric forms was first accomplished by Prelog & Wieland (1944). It is interesting to note that this was the first amine, chiral solely due to the difficulty of inversion at N, to be resolved.…”
Section: Introduction the Title Compound First Prepared Bymentioning
confidence: 97%
“…Because of this hindered inversion of the bridgehead nitrogen atoms, TB is chiral and can exist in two enantiomeric forms, R,R and S,S (Figure 1). They were first resolved in 1944 by Prelog, [4] who has also found that TB undergoes racemization in diluted acids. The suggested mechanism of the process involves a cleavage of the CH 2 bridge in the corresponding monocation leading to the formation of iminium salt followed by recyclization (Scheme 1).…”
Section: Introductionmentioning
confidence: 97%
“…The resolution of Tröger's base into its pure enantiomeric forms was first accomplished by Prelog and Wieland in 1944 by liquid chromatography using a chiral dlactose column, making Tröger's base the first chiral tertiary amine devoid of non-nitrogen stereogenic centers to be optically resolved. [3] The unique chirality of Tröger's base has since been exploited in the field of chromatography, and it frequently appears as a standard racemic mixture for the development of chiral separation methods. [4][5][6] The synthetic path to symmetric Tröger's bases, those decorated with the same substituents on each ring, is straightforward and mimics the original procedure discovered by Tröger.…”
Section: Introductionmentioning
confidence: 99%